A evolução do elemento indo-europeu -sk-: assimetria e gramaticalização - Johnnatan Ivens Antunes Nascimento (2016)
This text describes diacronically the evolutionary path of the indo-european suffix -sk-, from its development in indo-european languages, focusing on romance languages, specially the Brazilian Portuguese. It also demonstrates the relationship between -sk- and the Latin suffix -sc-, which ocurred in inchoative/causative verbs. Based on that, the focus is on the relationship between -sc- and parasynthesis in Portuguese. It is a process of joining two morphes representing a single morpheme, as in envelhecer 'to grow old' and embranquecer, 'to become white'. This relationship conects the Latin suffix -sc- to the Portguese -c-, that appears in parasynthetic formations. Finaly, in the descriptive part of this work, verbs like branquear 'to become white' and endoidar 'to become crazy', formed with the same roots that embranquecer and endoidecer are formed and with the same meaning. From these descriptive section, the thext is linked to a theoretical approach, focusing on the development of the latin suffix -sc- into the Brazilian Portuguese, under the Grammaticalization perspective. In order to do so, the evolution of -sk- into latin, generating the inchoative -sc- is seen as Grammaticalization. The co-ocurrence of the suffixd verbs in -sc- and verbs formed with this suffix plus a prefix in Latin, such as calescere 'to become hot' and incalescere, same meaning, these last forms gave rise to the parasyntetic structures found in Portuguese. A trace [+inchoative] is established. It first existed in the -sc- suffix, but later it was shared by the prefix and the suffix, demonstranting how the parasythesis emerged. Then, the hipothesis that parasynthetic verbs like endoidecer were the source to formations as endoidar, without suffix is presented. Furthermore, to explain how the prefixed forms are originated from the parasynthetic ones, the symmetry breaking mechanism is approached. Symmetry tends to be avoided, because it propitiates choicepoints. Parasynthetic structures are symmetric, because they exibit two morphes for a single morpheme, causing instability to language system. To eliminate it, the symmetry breaking appears